Pengaruh Teknik Parafrase Terhadap Kemampuan Menulis Karya Ilmiah Siswa Kelas XI SMA Negeri 4 Binjai - Arroyo Tita Angraini; Joharis Lubis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to (1) explain the writing skills of class XI students at SMAN 4 Binjai before using the paraphrase technique, (2) explain the writing skills of class XI students at SMAN 4 Binjai after using the paraphrase technique, (3) describe the influence of paraphrasing techniques on the ability to write scientific papers at SMAN 4 Binjai. The method that used in this study is an experimental method with a one group pre-test post-test design. The population used in this study included all 170 students in class XI IPA at SMA Negeri 4 Binjai and the sample in this study was students in class XI IPA 1 with a total of 35 students. Data analysis techniques that researchers use to support this research are quantitative data by testing analysis requirements, homogeneity tests, and hypothesis testing. The results showed that the average results of students' paper writing skills before using the paraphrasing technique had a score of 53.97. For the average value obtained by students after using the paraphrasing technique, they obtained a score of 82.62 and belonged to the good category. Overall it can be concluded that teaching by using the paraphrasing technique has a positive effect on the ability to write scientific papers in class XI students of SMA Negeri 4 Binjai.